2021
DOI: 10.3390/f12040450
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antecedent Fire Severity on Reburn Severity and Fuel Structure in a Resprouting Eucalypt Forest in Victoria, Australia

Abstract: Research highlights—Feedbacks between fire severity, vegetation structure and ecosystem flammability are understudied in highly fire-tolerant forests that are dominated by epicormic resprouters. We examined the relationships between the severity of two overlapping fires in a resprouting eucalypt forest and the subsequent effect of fire severity on fuel structure. We found that the likelihood of a canopy fire was the highest in areas that had previously been exposed to a high level of canopy scorch or consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 76 publications
0
15
0
2
Order By: Relevance
“…High-severity fire has been found in some cases to promote denser regrowth in understoreys and consequent positive feedbacks to flammability (e.g. (Collins et al 2021b)). Severity data were unavailable for much of the period of our study, but the increased flammability that we measured may be broadly characterised as a response to prescribed burning, as that accounts for more than 80% of fire in the majority of our forested study area (Boer et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…High-severity fire has been found in some cases to promote denser regrowth in understoreys and consequent positive feedbacks to flammability (e.g. (Collins et al 2021b)). Severity data were unavailable for much of the period of our study, but the increased flammability that we measured may be broadly characterised as a response to prescribed burning, as that accounts for more than 80% of fire in the majority of our forested study area (Boer et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Trends in climate variability will likely have a number of impacts on the carbon cycle of the region. A major risk for forest ecosystems is recurrent fires during recovery from the previous fires, with studies finding significant negative impacts on ecosystem function for both obligate seeder (D. M. J. S. Bowman et al., 2014) and resprouter‐dominated communities (Collins, Hunter, et al., 2021; Fairman et al., 2017). This risk may be compounded by longer recovery periods after fire due to frequent extreme heat and drought events.…”
Section: Discussionmentioning
confidence: 99%
“…Both the increased understory cover and the reduced vertical separation in forests after high severity fire provide a mechanism to explain the results of Barker and Price (2018), who found that high severity fire in dry sclerophyll forests of eastern Australia is more likely after previous high severity fire over a range of times since fire from five to thirty years. This is supported by Collins et al (2021), who found that the difference in basal and epicormic resprouting patterns after different fire severities resulted in variations in canopy structure and vertical connectivity in Victorian Eucalypt forests 6-12 years post-fire. There was greater fuel connectivity after high severity fire, which was then associated with further high severity in a subsequent fire.…”
Section: Discussionmentioning
confidence: 61%
“…This is supported by Collins et al . (2021), who found that the difference in basal and epicormic resprouting patterns after different fire severities resulted in variations in canopy structure and vertical connectivity in Victorian Eucalypt forests 6–12 years post‐fire. There was greater fuel connectivity after high severity fire, which was then associated with further high severity in a subsequent fire.…”
Section: Discussionmentioning
confidence: 99%